Epigonic Totalitarianism in Russia (Politeja, 2019)
This article aims to identify the dynamics of the Russian political regime and explain its sources. The article addresses the research problems of what the dynamics of the Russian political regime entailed from the beginning of the Russo- Ukrainian war to the end of Putin’s third presidential term as well as the sources of the dynamics. It verifies the hypothesis that the authoritarian regime started adopting totalitarian elements of the party-state apparatus, totalitarian political gnosis, and mass and controlled social mobilization in time. There were very strong neo-imperial tendencies and post-imperial nostalgia which contributed to the epigonic nature of the system changes. However, qualitative change of the system has not occurred. The research makes use of source analysis and the technique of conceptual content analysis to gather the data necessary to evaluate the changes in the Russian political regime in the mentioned aspects. The researchers triangulated mass media information and monographs and adopted the principle of theoretical sampling to verify the information necessary to recognize the values of the three indicators. Furthermore, the research applies three dual typologies of the essential features of political regimes to differentiate between the state of the system during individual ellipses of bifurcation.